Translation and cultural adaptation of the web and printed versions of a decision aid to support men's prostate cancer screening choice - Baptista, Sofia (2019)
INTRODUCTION: Prostate cancer is one of the most frequent cancers among men. However, screening for prostate cancer carries many risks and a small benefit. Thus, based on the available evidence, most medical organisations advocate a shared decision-making process, in which decision aids may play an important role. Nevertheless, to date there is no such instrument to be used by Portuguese men. Our goal is to translate and perform the cultural adaptation of an English language prostate cancer screening decision aid called 'Making the best choice', in web and printed formats, which has been developed and tested by a workgroup from Georgetown University (USA). METHODS AND ANALYSIS: Culturally and technically inappropriate recommendations in the original decision aid will be reviewed by the process coordinator and a linguistic expert. Two forward translations from English to Portuguese will be done, followed by a back-translation and an independent expert review. We will further improve the decision aid through an iterative process of data collection, data analysis and decision aid review. Individual semistructured cognitive interviews will be conducted and audiotaped with 55-69-year-old men recruited from the local community (urban and suburban) of Oporto district. We plan a total sample size of 30 participants (15 interviews per format). All participants will receive written information about the study and will sign individual consent forms. After verbatim transcription of the audiofiles, a thematic categorical analysis will be conducted using Ligre Software. ETHICS AND DISSEMINATION: The study protocol was approved by the Health Ethics Committee from Centro Hospitalar de São João/Faculdade de Medicina da Universidade do Porto. Results from this study will be disseminated in peer-reviewed publications and the Portuguese decision aid will available to Portuguese men.